2003
DOI: 10.1021/bi0206560
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Reactivation Kinetics of Homodimeric Triosephosphate Isomerase from Unfolded Monomers

Abstract: Homodimeric triosephosphate isomerases from Trypanosoma cruzi (TcTIM) and Trypanosoma brucei (TbTIM) have markedly similar catalytic properties and 3-D structures; their overall amino acid sequence identity is 68% and 85% in their interface residues. Nonetheless, active dimer formation from guanidinium chloride unfolded monomers is faster and more efficient in TcTIM than in TbTIM. The enzymes thus provide a unique opportunity for exploring the factors that control the formation of active dimers. The kinetics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 36 publications
7
48
0
Order By: Relevance
“…In a second step of the experiment, the denaturing mixture was diluted in buffer containing different concentrations of the studied compounds. As previously shown by Zomosa-Signoret et al 22 , the removal of the denaturant, GdnHCl, by dilution leads to the refolding and association of the monomers to form the catalytically active dimer. This reaction can be followed, by measuring the appearance of activity through time.…”
Section: The Action Of Compounds 2 and 3 On Different Timssupporting
confidence: 52%
“…In a second step of the experiment, the denaturing mixture was diluted in buffer containing different concentrations of the studied compounds. As previously shown by Zomosa-Signoret et al 22 , the removal of the denaturant, GdnHCl, by dilution leads to the refolding and association of the monomers to form the catalytically active dimer. This reaction can be followed, by measuring the appearance of activity through time.…”
Section: The Action Of Compounds 2 and 3 On Different Timssupporting
confidence: 52%
“…3). In the absence of BSA, and in consonance with other works [17][18][19], we observed that the extent of reactivation increased with protein concentration indicating that the rate of reaction 2 is central in the reactivation of LdTIM.…”
Section: Reactivation Of Ldtimsupporting
confidence: 92%
“…In a second step of the experiment, the denaturing mixture was diluted in buffer containing different concentrations of the compound. As previously shown by 24 , the removal of the denaturant by dilution leads to the refolding and association of the monomers to form the catalytically active dimer. This reaction can be followed by measuring the appearance of activity through time.…”
Section: Effect Of Compounds 1 and 2 On The Activity Of Different Timsmentioning
confidence: 59%